Author Correction: Cold-induced epigenetic programming of the sperm enhances brown adipose tissue activity in the offspring. (November 2018) - Sun, Wenfei; Dong, Hua; Becker, Anton; Dapito, Dianne; Modica, Salvatore; Grandl, Gerald; Opitz, Lennart; Efthymiou, Vissarion; Straub, Leon; Sarker, Gitalee; Balaz, Miroslav; Balazova, Lucia; et al.
In the version of this article originally published, the months on the axis labeled projected month of conception in Fig. 1a were out of order. April and March should have been the first and last months listed, respectively. The error has been corrected in the print, PDF and HTML versions of this article.